(3v-1)(5-v)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

3v-1=0

5-v=0

Set the first factor equal to 0.

3v-1=0

Add 1 to both sides of the equation.

3v=1

Divide each term by 3 and simplify.

Divide each term in 3v=1 by 3.

3v3=13

Cancel the common factor of 3.

Cancel the common factor.

3v3=13

Divide v by 1.

v=13

v=13

v=13

v=13

Set the next factor equal to 0.

5-v=0

Subtract 5 from both sides of the equation.

-v=-5

Multiply each term in -v=-5 by -1

Multiply each term in -v=-5 by -1.

(-v)⋅-1=(-5)⋅-1

Multiply (-v)⋅-1.

Multiply -1 by -1.

1v=(-5)⋅-1

Multiply v by 1.

v=(-5)⋅-1

v=(-5)⋅-1

Multiply -5 by -1.

v=5

v=5

v=5

The final solution is all the values that make (3v-1)(5-v)=0 true.

v=13,5

Solve using the Square Root Property (3v-1)(5-v)=0